Innovative learning environments and new materialism: A conjunctural analysis of pedagogic spaces. Issue 8 (3rd July 2017) - Charteris, Jennifer; Smardon, Dianne; Nelson, Emily
Abstract: An Organisation for Economic Cooperation and Development research priority, innovative learning environments (ILEs) have been translated into policy and practice in 25 countries around the world. In Aotearoa/New Zealand, learning spaces are being reconceptualised in relation to this policy work by school leaders who are confronted by an impetus to lead pedagogic change. The article contributes a conjunctural analysis of the milieu around the redesign of these education facilities. Recognising that bodies and objects entwine in pedagogic spaces, we contribute a new materialism reading of ILEs as these are instantiated in New Zealand. New materialism recognises the agential nature of matter and questions the anthropocentric narrative that frames the post-enlightenment conception of what it means to be human. The decentring of human subjects through a materialist ontology facilitates a consideration of the power of objects to affect the spatial politics of learning environments. The article traces a relationship between the New Zealand strategic plan for Education 2015–2021 and principal conceptions of ILE as the lived spaces of this policy actualisation and the disciplinary/control society conjuncture. Informed by theories of spatial practice, we argue that principals' understandings of 'space' are integral to pedagogic approaches within open-plan spaces. A conjunctural analysis can expand the capacity to act politically. By examining the complex conditions of a political intervention, in this case ILEs, we trace the displacements and condensations of different sorts of contradictions, and thus open up possibilities for action.